LAYAKKAH ANDA SEBAGAI PEMIMPIN? - Suryadi, Suryadi (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
A leader method would be easily distorted when their moral acts are not based on the living point of view specified by Allah and Rasul. The commitment regarding the right thing for such leader would not last for long. The true leader is a leader whose actions are properly based on their function as Khalifatullah and Abdullah. The true leaders are aiming for Ridho AllahÂ as the expression of their beliefs.Key word: Leader; moral method; Ridho Allah